Psychological and Social Factors Influencing Adolescents’ Perception of Physical Activity - Shodiyevich, Xakimov (Jurnal Psikologi, 2025)
The psychological and social factors influencing adolescents' acceptance of physical activity have a significant impact on their physical development, health, and overall well-being. This article analyzes the psychological factors affecting the acceptance of physical activity in adolescents, including motivation, self-awareness, stress management, as well as social factors such as family support, peer influence, and the impact of the group environment. This study analyzes psychological and social factors influencing adolescents’ engagement in physical activity through qualitative content analysis of existing literature, employing comparative and analytical methods. Key psychological aspects such as motivation, self-awareness, and stress management, alongside social influences like family and peer support, are examined. Results show that higher self-confidence, intrinsic motivation, effective stress coping, and strong social support significantly enhance adolescents’ participation in physical activity. The study concludes that both psychological traits and social environments critically shape adolescents’ attitudes toward maintaining an active lifestyle and promoting overall well-being.